POLITENESS AND COMPLIMENTING WITHIN AN ALGERIAN CONTEXT -A SOCIO-PRAGMATIC ANALYSIS- - Meryem, Sekkal Babou (PEOPLE: International Journal of Social Sciences, 2018)
Complimenting is the speech act that reflects some politeness strategies in every day’s life. Its main characteristic is expressing positive appraisal in order to build up new relationships or reinforce current relationships and give them support. It is commonly used or found in various circumstances and within different moods i.e. in happy and sad events and temperaments. Actually, the satisfaction which generally results from receiving a compliment may lead to the conviction that the person who uses compliment is in a way or another is polite and friendly or at least tries to make the addressee feels more relaxed. The research at hand aims at investigating the way Algerians make, receive, accept and reject compliments. The methodology followed is based on two main tools namely; participant observation and questionnaire tool so as to be able to capture the phenomenon as it occurs. The results shows that complimenting in Algeria may result in either accepting or rejecting as it can lead to the employment of some religious terms so as to avoid the happening of bad incident.